KAJIAN AUDIT REPORT LAG DARI PERSPEKTIF TATA KELOLA KORPORASI: EKSPLORASI PERAN KUALITAS AUDIT SEBAGAI VARIABEL MODERASI - Saputra, Dede Yudha; Zaitul, Zaitul; Mahendri, Meihendri; Yulistia Muslim, Resti; Ilona, Desi (POLITEKNIK LP3I JAKARTA, 2024)
Audit report lag is an important aspect of accounting quality. However, there is a lack of previous studies investigating why companies have auditors sign financial reports late; others need less time to do so. This study determines the factors affecting the audit report lag from a corporate governance perspective during COVID-19. In addition, the role of audit quality as a moderating variable between corporate governance and audit report lag is also rare. Ninety-seven publicly listed companies participated in this study. The secondary data from 2019 to 2021 were involved. Agency theory is applied to explain the phenomenon. Moderated regression analysis is applied to gain the result. The result shows that audit tenure significantly affects the audit report lag. In addition, audit quality plays a moderating variable between board size and audit report lag. Hence, audit quality also moderates the relationship between audit tenure and audit report lag. The research has practical implications for reducing audit tenure by reducing auditing report lag. In addition to practical implications, this research also implies the theory where the results of this research can be explained by the agency theory in which to improve the quality of accounting information through the timely submission of financial reports and to shorten the time of signing an audit opinion through the governance mechanisms. Keywords: Size Of The Board Of Commissioners; Board Commissioner Meeting Frequency; Audit Tenure; Audit Opinion; And Audit Quality; Audit Report Lag